A modified "gel-blowing" strategy toward the one-step mass production of a 3D N-doped carbon nanosheet@carbon nanotube hybrid network for supercapacitors. Issue 16 (13th February 2019) - Zhou, Weiwei; Du, Yu; Zeng, Jinjue; Liu, Fei; Zhu, Yongming
Abstract : We have realized the synchronous and large-scale synthesis of 1D CNTs on 2D N-doped carbon nanosheets (NCNS) by a one-step annealing of a gel precursor. Abstract : In this work, we have realized the synchronous and large-scale synthesis of one-dimensional (1D) carbon nanotubes (CNTs) on two-dimensional (2D) N-doped carbon nanosheets (NCNS) by a one-step annealing of a Ni-containing gel precursor. Upon heating, the gel is "blown" into large-sized 2D NCNS with uniformly embedded Ni nanoparticles that can catalyze the in situ CNT growth, forming a three-dimensional (3D) N-doped carbon nanosheet@carbon nanotube (NCNS@CNT) hybrid. Different from our previous "gel-blowing" strategy for 2D nanosheets, the modified "gel-blowing" strategy is capable of producing 3D architecture by employing a new complexing agent and introducing ethanol as a carbon source. Importantly, this method can be easily scaled up by annealing more gel precursors with an increased amount of ethanol. The introduction of CNTs endows NCNS@CNTs with higher quality and larger specific surface area (SSA) than pure NCNS. Consequently, the electrochemical performance of 3D NCNS@CNTs is much superior to that of 2D NCNS and found to be related with the annealing temperature. The optimized NCNS@CNTs can deliver a specific capacitance of 124 F g −1 at 1 A g −1 and maintain 88% of their initial value after 10 000 cycles at 1 A g −1 . Furthermore, NiO nanosheets are deposited on the NCNS@CNT framework to study its function as a conductive host. The as-fabricated hybrid electrode exhibits a high specific capacitance of 660 F g −1 at 1 A g −1 and 532 F g −1 at 20 A g −1, which is also better than its counterpart using NCNS as substrates. This method provides a simplified and low-cost way towards the mass production of NCNS@CNTs for energy application and beyond.